Kepastian Hukum Pembagian Harta Bersama Karena Perceraian Terkait Harta Bersama Yang Dikuasai Oleh Salah Satu Pihak - Widagdo, Sarastyo Dwi; Turhamun, M.Slamet; Yani, Ahmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In divorce, of course, there are parties who decide to divorce. There is a difference in mention between those who file a divorce case from the husband's side, and those who file a divorce case from the wife's side. The person or legal subject who files a divorce case in court is referred to as the parties or parties to the case. In the case of divorce, if the person filing for divorce is the husband, then the husband is then referred to as the